Gene polymorphisms of inflammatory factors in liver cirrhosis - Xiao, Sailan; Pan, Xiongfeng; Huang, Xun; Liu, Yamin; Wen, Shi Wu; Liu, Aizhong (Frontiers in Genetics, 2023)
Background: Studies on the association between gene polymorphisms of various inflammatory factors and liver cirrhosis have been inconsistent. The purpose of this study was to comprehensively summarize the available evidence on the association between gene polymorphisms of inflammatory factors and liver cirrhosis through a systematic review. Methods: We searched databases of PubMed, EMBASE, Web of Science and the Cochrane Library for relevant articles published not later than September 2022. A systematic review and meta‐analysis were performed to investigate the association between gene polymorphisms of various inflammatory factors and liver cirrhosis. Odds ratios (OR) and 95% confidence intervals (CI) were used to assess the strength of association. Results: A total of 43 articles were included in the systematic review and of them, 22 articles were included in the meta‐analysis. The gene polymorphisms of IL-10 GA+AA vs GG (OR = 1.43, 95% CI = 1.12–1.83), IL-10 AA vs GG (OR = 2.03, 95% CI = 1.36–3.02), IL-18 GG vs CC (OR = 3.84, 95% CI = 1.29–11.40), and TGF-β1 T vs C (OR = 2.52, 95% CI = 1.42–4.48), IFN-γ T vs A (OR = 1.98, 95% CI = 1.32–2.98) were associated with liver cirrhosis significantly and no association was observed in other gene polymorphisms included in the meta‐analysis. Besides, the review of inflammatory factors gene polymorphisms that were only reported by one study indicated 19 gene polymorphisms were risk factors and 4 gene polymorphisms were protective factors for liver cirrhosis, while the association between other 27 gene polymorphisms and liver cirrhosis were not statistically significant. Conclusions: This study suggests that IL-10, IL-18, TGF-β1 and IFN-γ were potentially associated with the risk of liver cirrhosis susceptibility. These findings may provide comprehensive evidence for genetic susceptibility and immunogenetic pathology of liver cirrhosis.